2015
DOI: 10.3928/01477447-20150204-92
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of a Tibial Osteochondral Allograft to Restore a Large Glenoid Osteochondral Defect

Abstract: Osteochondral disease of the glenoid is a well-known cause of shoulder pain and disability in young and active patients. The etiology can be multifactorial, and disease severity can exist across a wide spectrum. Symptoms can often interfere with athletic performance, job responsibilities, and activities of daily living. Although a number of cartilage restoration techniques exist for other joints, such as the hip, knee, ankle, and elbow, restorative options for glenoid osteochondral defects are currently limite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Characteristics of the 14 studies meeting all inclusion criteria can be found in Table 1 . 1-6,17-24 There were 6 retrospective case series, 7 case reports, and 1 prospective case series. This resulted in a total of 100 shoulders in 98 patients.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Characteristics of the 14 studies meeting all inclusion criteria can be found in Table 1 . 1-6,17-24 There were 6 retrospective case series, 7 case reports, and 1 prospective case series. This resulted in a total of 100 shoulders in 98 patients.…”
Section: Resultsmentioning
confidence: 99%
“…The etiology of cartilage injury within the glenohumeral joint can include previous surgery, trauma, osteochondritis dissecans, infection, avascular necrosis, inflammatory arthritis, glenohumeral joint instability, rotator cuff arthropathy, osteoarthritis, and chondrolysis. 1 Patients with glenohumeral cartilage or osteochondral defects may present with a variety of symptoms, including generalized achiness exacerbated with activity, progressive pain to the point of limiting sport activities, constant deep shoulder pain, sharp pain following an acute injury, or progressive crepitation associated with increasing pain. 1-6…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the literature, the mean glenoid defect size ranges from 1.12 to 2.73 cm 2 , whereas the mean humeral defect size ranges from 4.22 to 6.00 cm 2 (Table 2). 3,[13][14][15][16] The mean articular cartilage depth of the humerus has been reported to be 1.24 mm, ranging from approximately 1.3 mm centrally and thinning to less than 1 mm along the periphery, and the mean depth of the glenoid fossa has been reported to be 1.88 mm. 17 Regeneration of lost cartilage has been the ultimate goal for treatment of articular cartilage defects of the glenohumeral joint.…”
Section: Discussionmentioning
confidence: 99%
“…Debridement and bone marrow stimulation may not provide a satisfied long-term prognosis, especially in young active patients [ 12 ]. Although osteochondral grafts demonstrate satisfactory outcomes, the allografts face a limited application ascribed to immune rejection and the risk of disease transmission [ 13 , 14 ], and the autografts will cause additional physical trauma [ 15 , 16 ]. Therefore, there need alternative therapies for osteochondral defects urgently.…”
Section: Introductionmentioning
confidence: 99%